2017
DOI: 10.1016/j.ygyno.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Surgical readmission and survival in women with ovarian cancer: Are short-term quality metrics incentivizing decreased long-term survival?

Abstract: Objectives To determine the association between treatment with neoadjuvant chemotherapy (NACT) or primary debulking surgery (PDS) and readmission after surgical hospitalization as well as overall survival among women with stage IIIC epithelial ovarian cancer (EOC). Methods We identified incident cases of stage IIIC EOC treated with both chemotherapy and surgery in the National Cancer Database (NCDB) from 2006-2012. 30-day readmissions were categorized as planned or unplanned. Log binomial models were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…Tumor biology of patients with higher preoperative disease burdens is likely different from that of patients with less disease, which may overwhelm the advantage of optimal, aggressive cytoreduction in this select group of patients, but not others . Patients with International Federation of Gynecology and Obstetrics (FIGO) stage III and IV disease were grouped in prospective trials, but 2 large observational studies suggest that women with FIGO stage III disease may benefit from primary surgical cytoreduction, while those with FIGO stage IV disease do not . Histologic tumor types, such as clear cell, low‐grade serous and mucinous tumors, are now known to be relatively chemotherapy resistant but were included in several of the NACT trials.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Tumor biology of patients with higher preoperative disease burdens is likely different from that of patients with less disease, which may overwhelm the advantage of optimal, aggressive cytoreduction in this select group of patients, but not others . Patients with International Federation of Gynecology and Obstetrics (FIGO) stage III and IV disease were grouped in prospective trials, but 2 large observational studies suggest that women with FIGO stage III disease may benefit from primary surgical cytoreduction, while those with FIGO stage IV disease do not . Histologic tumor types, such as clear cell, low‐grade serous and mucinous tumors, are now known to be relatively chemotherapy resistant but were included in several of the NACT trials.…”
supporting
confidence: 93%
“…Cancer December 15, 2019 with FIGO stage IV disease do not. 8,9 Histologic tumor types, such as clear cell, low-grade serous and mucinous tumors, are now known to be relatively chemotherapy resistant but were included in several of the NACT trials. In aggregate, the evidence from observational data conflicts with evidence presented by randomized trials, suggesting that there are indeed populations of patients in whom NACT confers a benefit, but others may be better served with an up-front surgical approach.…”
mentioning
confidence: 99%
“…At a time when surgeons are judged on the basis of theater times, hospital stay, complications, and readmission rates, it is not surprising that surgeons manifest considerable reluctance to operate on higher risk patients with extensive tumor dissemination that will require more complex surgery 2023. A 30-day readmission rate has been internationally proposed as a metric of surgical quality, something that has caused an ongoing clinical concern in the primary treatment of advanced EOC 22.…”
Section: Discussionmentioning
confidence: 99%
“…ovarian cancer. [7][8][9] There is a high burden associated with hospital readmissions for patients, insurance providers, and the healthcare system. We assessed patient, hospital, and operative characteristics to identify predictors of readmission so that care and payment models might be better optimized at index hospitalization.…”
Section: Patient and Hospital Characteristics Of Cohorts With And Wmentioning
confidence: 99%
“…Previous studies have found minimal correlation between rehospitalization rates and overall survival following debulking surgery but have been mostly limited to the initial 30 days following discharge from index hospitalization. [7][8][9][10] Although postoperative readmission does not appear to correlate with surgical quality for patients with ovarian cancer, it does represent additional burden on the patient and healthcare system in terms of resource utilization. This burden has been thoroughly characterized for the first 30 days postoperatively, but increased understanding of outcomes beyond the first 30 days could help to guide treatment and payment model decisions for this population.…”
Section: Introductionmentioning
confidence: 99%